ADA2 deficiency due to a novel structural variation in 22q11.1. Issue 6 (28th March 2019) - Grossi, Alice; Cusano, Roberto; Rusmini, Marta; Penco, Federica; Schena, Francesca; Podda, Rosa A.; Caorsi, Roberta; Gattorno, Marco; Uva, Paolo; Ceccherini, Isabella
Abstract :